Documentation of Student Admission Procedures or College Students on The Job Training at Batam Aero Technic - Dina Setiawati Permata Sari (MID Publisher International, 2023)
This study report discusses the documentation for the admission procedure of students or college students On the Job Training (OJT) at Batam Aero Technic. The background in taking this research topic is due to the irregularity of the admission procedures for students or On Job Training (OJT) college students at Batam Aero Technic. The purpose of this study is to find out the procedure for accepting students or college students On the Job Training (OJT). This research used a descriptive method and the data collection method was conducted by interview method and documentation method. The result of this study is an overview or documentation that is poured through a flowchart regarding the stages of student admission procedures or On the Job Training (OJT) for college students at Batam Aero Technic.